Theological Implications of the Existence of "Offensive" Animals and the Ascetical Opportunities They Provide. - Nosal, Andrew P. (Zygon: Journal of Religion & Science, 2025)
Charles Darwin was unimpressed by the natural theology of his time, owing to his observations of suffering in nature and, famously, the particularly elegant viciousness of parasitoid wasps (Ichneumonidae). Presented here is a theological reflection, from a largely Eastern Orthodox perspective, about these wasps and other hard-to-love animals that exhibit behaviors so disturbing or "offensive" that their mere existence may seem incompatible with the existence of an all-knowing, all-loving, and all-powerful Creator-God. These include infanticide in lions, siblicide in boobies, intrauterine cannibalism in sharks, and brood parasitism in cuckoos. These behaviors are obligate, intrinsic to these species— intrinsic to their design. I consider how these animals became so "offensive," including alteristic (Creation being drastically altered, namely, corrupted, by the human Fall into sin) and non-alteristic explanations. I conclude by reflecting on what should be the Christian response to these creatures, including how they present unique ascetical opportunities for Christians to cultivate an all-embracing cosmic love for Creation.